Recasting Shakespearean Heroes in Indian films: A Study on three Bollywood films Omkara, Maqbool and Haider - Boruah, Rimjim; Choudhury , Madhulina (International Journal of Psychosocial Rehabilitation, 2019)
It has been a common phenomenon of film producers and directors to have been inspired to cast a film after reading a text, be it a novel, play or a short story. It is seen that films often have similarities with a book. A common example to be seen in Indian scenario is the famous Bollywood film of Amir Khan, 3 idiots, an adaptation of Indian writer Chetan Bhagat’s novel Five Point Something. There are several other such examples. The film is not presented exactly as same as the novel, but the main gist is kept. Some films adopt new events and add new situations to cope up with the mindset of the one producing it and of its immediate audience. It is important to keep in mind that in a film which takes its inspiration from a book or any article, it has to blend up within two or three hours everything of the source. Social interpretation leads to thenewness in the re creation of the book in the form of the film. During interpretation of the film,sometimes the producer includes things to which he gives priorities. This is what one finds in the three films, Omkara, Maqbool and Haider which are the adopted versions of Shakespeare’s plays Othello, Macbeth and Hamlet respectively.